Analisis Daerah Rawan Kecelakaan (Black Site) Dan Titik Rawan Kecelakaan (Black Spot) Provinsi Lampung - Yogi Oktopianto; Siti Shofiah; Faishal Andhi Rokhman; Kanthi Pangestu Wijayanthi; Eka Krisdayanti (Borneo Engineering : Jurnal Teknik Sipil, 2021)
Traffic accidents are the main indicator of road safety levels. There were 2,225 traffic accidents throughout 2019 in Lampung Province with 724 deaths, 1240 seriously injured, and 2015 minor injuries. The research was conducted to the identification of the black site and black spot in Lampung Province. The method used in this research is the EAN, Z-score, Frequency of accidents method calculates accident-prone areas to get the value of the accident location (Black Site) and the Cumulative Summary method to identify the black spot. The results showed from 93 roads, there is 1 road which is the highest black link of each road status. The accident-prone area (black site) is Jalan Lintas Tengah Sumatra and accident-prone points (black spot) at KM 18-26 are influenced by land use, road geometric, and traffic signs.